ANATOMICAL ELABORATION OF GAVINI SHARIR (ATHARVAVEDA) WITH SPECIAL REFERENCE TO ADHOGAMI MUTRAVAHI DHAMANI - Thakur Pritamsing Chandansing; Shrikrishna Bhagwat Sachin; Jape Ravindra Ramdas; Humne Sankalp Ramrao; Kharat Ravindra Sahebrao (International Journal of Applied Ayurved Research, 2016)
The Ayurvedic Literature on Adhogami Dhamanis is compiled and studied. The exact divi-sion of Dhamani and detail study of Adhogat Dhamanis which are present in Abdomen is done. Out of them the two Mutravahi Dhamanis are described with all references. Then the Gavini Sharir is elaborated with its main reference from Atharvaveda and all commentaries compiled together to elaborate Gavini. All the opinions regarding their meaning, grammar in the paribhasha of Shloka to get the exact meaning are discussed. To go practically for the Anatomy cadaveric dissections were done and the observations were noted, these observa-tions are suggestive about the mixed up use of Dhamani word everywhere and the word is used for particular structure regarding the present topic. And the same is used at another place with a different meaning. Sometimes it was considered as artery, vein, lymphatic and sometimes even for the vessels attached to the viscera. To study the above points in depth, the histological study was also done and it also revealed that similarities are more than the differences in artery and Ureter. The Sharir told in Atharvaveda has been elaborated by Sushruta by his own practical ap-proach.But the Gavini Sharir in Atharvaveda is not explained further by Sushruta. He had written about Adhogami Mutravahi Dhamani but didn’t use the word Gavini.There are still many confusions and dilemma about many things. This diversity should be united to make a certain conclusion. This study is to compile and analyze Gavini and Adhogami Mutravahi Dhamanis to evaluate these two are different or one and the same.